The effect of coffee consumption on the tnf-α level after submaximal exercise - Izzul Mujahidin; Rizky Darmawan; Muhammad Fath Alhaqqi Sanis Salamy; Nura Maulida Isna; Mohammad Fathul Qorib; Lilik Herawati (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Introduction: Exercise has become a lifestyle choice for many individuals seeking to maintain their health and reduce the risk of various diseases. However, exercising at a certain intensity requires significant energy expenditure and can lead to micro-damage in the muscles, which can be detected through several biomarkers, including levels of Tumor Necrosis Factor Alpha (TNF-α). This condition may adversely affect physical performance, leading some individuals to take supplements as a preventive measure. Additionally, post-workout caffeine consumption has gained popularity, particularly in the form of caffeinated drinks, in an effort to enhance physical fitness and productivity. Nevertheless, there is limited comprehensive research on the mechanisms by which caffeine affects post-exercise recovery.